2019
DOI: 10.1021/acs.jpcc.9b03686
|View full text |Cite
|
Sign up to set email alerts
|

Lithiation-Induced Structural Rearrangement and Stress Change in SiCO-Derived Porous Carbon: A First-Principles Study

Abstract: Silicon oxycarbide (SiCO)-derived porous carbon is a promising anode material for high-power lithium-ion batteries with large reversible capacity and high rate performance. In this work, porous carbon compounds with various morphologies are successfully reproduced by simulating the etching process of SiCO and then lithiation-induced structural rearrangement and stress change in porous carbon are investigated using first-principles calculations. Upon insertion of lithium, Si−C/O mixed-bond units are destroyed w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 45 publications
0
1
0
Order By: Relevance
“…72 However, it has been reported that local compressive stresses are generated in the lithiated systems resulting in the shortening of bond lengths and a higher bulk modulus. 77 This also means that the local stress generated can be used to measure the system's specific capacity. Moreover, it is observed that replacing oxygen with nitrogen in these systems makes it unattractive for lithium intercalation due to the highly covalent nature of Si–N bonds and the lower electron density of nitrogen atoms.…”
Section: First Principles Studiesmentioning
confidence: 99%
“…72 However, it has been reported that local compressive stresses are generated in the lithiated systems resulting in the shortening of bond lengths and a higher bulk modulus. 77 This also means that the local stress generated can be used to measure the system's specific capacity. Moreover, it is observed that replacing oxygen with nitrogen in these systems makes it unattractive for lithium intercalation due to the highly covalent nature of Si–N bonds and the lower electron density of nitrogen atoms.…”
Section: First Principles Studiesmentioning
confidence: 99%